ANANALYTICAL STUDY OF MARBLE CONSOLIDATION BY OXALATE PRECIPITATION USING DENSITY, FTIR AND POWDER-XRD MEASUREMENTS - Rihana Terzu; Edlira Baraj; Shun Yu; Christiane Förester; Holger Kropf; Kledi Xhaxhiu; Marsilda Come (Journal of Engineering & Processing Management, 2016)
Our recent study on consolidation of marble samples with the purpose of culture heritageprotection occurred by periodical calcium oxalate precipitation on top of quasi parallelepipedicsamples. The overall process consisting of three stages of treatment, starting with 5 % calciumacetate solution for 60 minutes at 20 ℃C, a draining step at 70 ℃ for 30 min, followed by a treatmentwith 5 % ammonium sulfate solution, it followed with the third stage which includes the treatmentwith 5% ammonium oxalate solution revealed a continuous density increace, determined usingethanol. As the natural samples had an initial density of 2.5871 g/cm3, it increased up to 2.6980g/cm3 for 50 times treatments. The precipitation of oxalate on top of calcium carbonate substrate, inform of calcite, revealed two distinguished infra-red bands, at 1316 cm-1and 1624 cm-1 unsymmetrically located around the carbonate one at 1426 cm-1.The intensity of the bands wasproportional to the number of treatments. The continuous surface coverage investigated in parallelby powder XRD evidenced the presence of whewellite crystallites deposited on top of calcite, andtheir intensity increasing as well with the number of treatments. This method exhibits a reliableoxalate coverage of marble sample surfaces which doesn’t influence considerably their watersolubility.
Keywords: calcium oxalate; marble; precipitation; density; FTIR; X-raypowderdiffraction (XRD)